Renewable energy powered organic ranking cycle - Velautham, Sanjayan; Abdul Aziz, Azhar; Mohd. Ghazali, Normah (Universiti Teknologi Malaysia, 2005)
This project studies the feasibility of an Organic Rankine Cycle (ORC) driven by solar thermal energy for sustainable power generation for small and medium sized commercial usage. An experimental study on a solar parabolic trough collector(PTC) for the use in the Organic Rankine Cycle, (ORC) is also focused here. ORC is principally a conventional Rankine Cycle that uses organic compound as the working fluid instead of water and it is particularly suitable for low temperature applications. Appropriate organic compound includes refrigerants and azeotropes. The ORC and the solar collector are sized according to the solar flux distribution in Malaysia. The location of study is Kota Kinabalu, highest yearly average of solar radiation, and Chuping, longest yearly average solar duration in the country for year 2003. The power generation system consists of two cycles, the solar thermal cycle that harness solar energy and the power cycle, which is the ORC that generates electricity. The solar thermal cycle circulates heat transfer fluid (HTF) in the cycle and harness thermal energy from the sun and transfers it to the organic compound in the ORC via a heat exchanger. The parabolic trough collector in this study is 1 meter in length and it consists of a curved mirror that concentrates sunlight on a tube with a heat transfer fluid (HTF) inside that runs parallel in the focal line of the mirror. The HTF selected in this analysis is water which is done during the experimental study also Therminol 55 and Therminol VP3 for the parametric study which is currently used for commercial thermal applications. For this research, 2 organic compounds were analyzed, R123 and Isobutene. These two compounds are optimized for selection. The results produced from the experimental study on the parabolic trough collector, (PTC), showing the variation of absorber temperatures and the value of power generated in terms of the solar collector designed is presented.